2011
DOI: 10.1109/tns.2011.2168827
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alpha Particles on the Electrical Characteristics of TiO$_{2}$ Memristors

Abstract: Titanium-oxide (TiO 2 ) memristors exposed to 1-MeV alpha particles exhibit only minor changes in the electrical response for ion fluencies up to 10 14 cm 2 . At higher fluence levels, virgin and off-state devices exhibit measurable increases in current conduction between the two platinum (Pt) electrodes. Analysis, supported by radiation transport and numerical device simulations, suggests that radiation-induced displacement damage in the TiO 2 film increases the density of oxygen vacancies, thereby altering b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 8 publications
4
30
0
Order By: Relevance
“…[216]. While at present the susceptibility of cation-based memory elements to displacement damage is not known, Barnaby et al [220] reported displacement damage effects in anion-based memristors, engineered with TiO 2 as the transition metal oxide. TiO 2 memristors, like most anionbased technologies, operate by controlling the distribution of oxygen vacancies in the TMO film.…”
Section: Displacement Damage Effects In Memristor Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…[216]. While at present the susceptibility of cation-based memory elements to displacement damage is not known, Barnaby et al [220] reported displacement damage effects in anion-based memristors, engineered with TiO 2 as the transition metal oxide. TiO 2 memristors, like most anionbased technologies, operate by controlling the distribution of oxygen vacancies in the TMO film.…”
Section: Displacement Damage Effects In Memristor Devicesmentioning
confidence: 99%
“…By contrast, the threats to anion-based RRAM posed by ionizing radiation were demonstrated to be minimal in [223] and [228]. In 2011, Barnaby et al reported that radiation-induced displacement damage was indeed the primary cause of memory loss in the TiO 2 memristors [220]. The devices reported on in [220] were fabricated by HP labs and exposed to 1-MeV alpha particles.…”
Section: Displacement Damage Effects In Memristor Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In work from Tong, et al TiO 2 devices were irradiated with 941-MeV Bi ions. Later work used 350-keV protons, neutrons [6] and 1-MeV alpha particles [2]. At Sandia, TaO x -based devices have been exposed to a variety of proton energies, including 4.5-MeV and 105-MeV, and to 800-keV silicon ions [3].…”
Section: Particle Simulationsmentioning
confidence: 99%